PENERAPAN METODE EOQ (ECONOMIC ORDER QUANTITY) UNTUK PENGEDALIAN STOK BARANG PADA APOTEK RIZEKY - Syakti, Firamon (Jurnal Bina Komputer, 2021)
Today's industry continues to develop with intense competition. with many new competing companies emerging in the same scope of industry. One pharmaceutical industry that continues to grow. So the need for good operational management so that the business continues to run. One of the good management by planning inventory that is efficient, effective, and economical. Pharmacy is included in the category of trading companies because its main activity is to purchase drug supplies from drug distributors / suppliers for resale to consumers without changing the shape or function of the goods. So the role of supplies is an important component in pharmacy operations. Rizeky Pharmacy is one of the pharmacies in Ogan Kemering Ilir Regency which coordinates pharmaceutical services for customers. The problem that is often faced by Rezeky Pharmacy is often the lack of availability of certain types of drugs which impact on the disruption of the drug sales process. Not only that for some types of drugs have excess inventory one of them expired drug because the storage process is too long. The solution to overcome the problem is to use the Economic Order Quantity method. So that it can be known when the optimal ordering point, what is the frequency of purchases within a certain period, how much stock is a safety stock, and time to repurchase drug supplies. And can find out how much savings the total cost of inventory from the Pharmacy